2021
DOI: 10.3389/fgene.2021.692356
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Trait Single-Step GBLUP Improves Accuracy of Genomic Prediction for Carcass Traits Using Yearling Weight and Ultrasound Traits in Hanwoo

Abstract: There has been a growing interest in the genetic improvement of carcass traits as an important and primary breeding goal in the beef cattle industry over the last few decades. The use of correlated traits and molecular information can aid in obtaining more accurate estimates of breeding values. This study aimed to assess the improvement in the accuracy of genetic predictions for carcass traits by using ultrasound measurements and yearling weight along with genomic information in Hanwoo beef cattle by comparing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 55 publications
4
7
0
Order By: Relevance
“…These findings were also in concordance with those reported by Mehrban et al [ 14 ], who applied the LR method to evaluate carcass traits in Hanwoo cattle using four evaluation models and showed that using genomic information and additional phenotypic information from highly genetically correlated traits is a suitable tool to improve the prediction accuracy.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings were also in concordance with those reported by Mehrban et al [ 14 ], who applied the LR method to evaluate carcass traits in Hanwoo cattle using four evaluation models and showed that using genomic information and additional phenotypic information from highly genetically correlated traits is a suitable tool to improve the prediction accuracy.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our results, several previous studies have proved the superiority of ssGBLUP over traditional BLUP approaches in various livestock since it was proposed [ 7 , 18 , 32 , 33 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Moreover, in Hanwoo cattle studies, the accuracies obtained from single-step models were found to be higher than those from pedigree-based and multi-step methods for carcass traits [ 11 , 12 , 13 , 14 , 15 , 51 ] and body measurement traits [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, no study has been published on the genomic evaluation of Hanwoo based on a large number of genotyped cows, steers, and young animals. Recently, Mehrban et al (2021) demonstrated the enhanced accuracy of single-step genomic prediction using a multi-trait model compared to that using a single-trait model.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the incorporation of genome-wide SNP panels into genetic evaluation models enables us to estimate the genomic breeding value (GEBV) that results in an improved accuracy of genomic prediction and an increased selection response for the traits of interest in cattle [ 14 ]. In recent years, the importance of genomic selection as a promising tool for gains in the accuracy of predictions compared with conventional genetic methods for carcass traits in Hanwoo breeding programs have been investigated in several studies [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The objective of the present review is to summarize studies concerning the identification of genomic regions and respective candidate genes and their corresponding pathways connected to carcass and growth traits in Hanwoo cattle.…”
Section: Introductionmentioning
confidence: 99%